Tradisi Kuda Lumping Guna Menciptakan Kerukunan Antar Masyarakat Di Desa Kulu Kajen Pekalongan - Sutama, Duratul Mufidah; Khasanah, Eka Amalia (IAINU Kebumen, 2023)
The kuda lumping tradition is one of the traditional Javanese arts that is still preserved today. This tradition is not only an art form, but also has positive values, one of which is the value of harmony. Harmony in diversity and religious moderation also bring the village of kulu kajen pekalongam to have an attitude of tolerance. This article aims to describe several things that can be used as a guide in the framework of the Kuda Lumping Tradition in order to create inter-community harmony in the village of Kulu Kajen Pekalongan which has a high spirit in preserving the tradition. This article will be comprehensive and specific about how the influence of residents on the Kuda Lumping Tradition in order to create harmony between communities in the village of Kulu Kajen Pekalongan. The method used is descriptive qualitative with a case study approach. The data collection technique is through observation and interviews.